Welfare effect of organic fertilizer use in Ghana - Edward Martey (Heliyon, 2018)
Most soils in Sub-Saharan Africa (SSA) are substantially degraded and are in need of restoration to enhance sustainable food production. This is a harder problem given that population is projected to increase with a corresponding increase in demand for food. Organic fertilizer can improve soil health by reducing the rate of nutrient leaching. However, there are limited studies on the economic effect of organic fertilizer use in SSA. Lack of in-depth understanding of the economics of organic fertilizer use and the welfare effect has the tendency to mislead policy. This paper employs the double selection and propensity score matching techniques to analyze the welfare impacts of organic fertilizer use. The results show that organic fertilizer use significantly increases the log of productivity and crop income by 1.43 and US$132 respectively and reduce total household expenditure, food expenditure and poverty by US$174, US$58, and 8% respectively. Disaggregation of the results based on landholdings and household size suggest that adopters of organic fertilizer with large farm size and household members recorded the lowest probability of being poor. Findings of this study demonstrate that the gains in the use of organic fertilizer can be consolidated with complementary input support and increased market participation.